2019
DOI: 10.1136/bmj.l6090
|View full text |Cite
|
Sign up to set email alerts
|

Variation in post-colonoscopy colorectal cancer across colonoscopy providers in English National Health Service: population based cohort study

Abstract: ObjectivesTo quantify post-colonoscopy colorectal cancer (PCCRC) rates in England by using recent World Endoscopy Organisation guidelines, compare incidence among colonoscopy providers, and explore associated factors that could benefit from quality improvement initiatives.DesignPopulation based cohort study.SettingNational Health Service in England between 2005 and 2013.PopulationAll people undergoing colonoscopy and subsequently diagnosed as having colorectal cancer up to three years after their investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
127
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(135 citation statements)
references
References 38 publications
5
127
0
3
Order By: Relevance
“…Specifically, they find higher rates of post colonoscopy cancers following privately provided colonoscopy, after controlling for certain confounding factors (adjusted odds ratio 1.63 (95% confidence interval 1.39 to 1.91), P<0.01). Rates were also higher among women, older people (aged ≥80), and in people with inflammatory bowel disease and diverticular disease 3…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Specifically, they find higher rates of post colonoscopy cancers following privately provided colonoscopy, after controlling for certain confounding factors (adjusted odds ratio 1.63 (95% confidence interval 1.39 to 1.91), P<0.01). Rates were also higher among women, older people (aged ≥80), and in people with inflammatory bowel disease and diverticular disease 3…”
mentioning
confidence: 96%
“…In a second paper, Burr and colleagues (doi:10.1136/bmj.l6090) quantify rates of colorectal cancer up to three years after a negative colonoscopy in England 3. They report a decreasing incidence of post-colonoscopy cancers over the period of investigation (from 9.0% in 2005 to 6.5% in 2013), but highlight statistically significant variation between colonoscopy providers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Burr and colleagues suggest that quality improvement is needed to reduce variation in colonoscopy performance, as measured by post-colonoscopy colorectal cancer (PCCRC) 1. This inter-hospital variation in colonoscopy quality has been known to UK gastroenterology since being shared by Roland Valori during the 2014 British Society of Gastroenterology (BSG) annual meeting.…”
mentioning
confidence: 99%
“…The rate at which people develop colorectal cancer within three years of a colonoscopy negative for cancer differs depending on which provider they use, with NHS screening providers performing better than non-NHS providers, a study has found 1…”
mentioning
confidence: 99%